2014
DOI: 10.1017/s1755691015000146
|View full text |Cite
|
Sign up to set email alerts
|

The seabed geomorphology and geological structure of the Firth of Lorn, western Scotland, UK, as revealed by multibeam echo-sounder survey

Abstract: This paper presents recently collected swath bathymetry from the Firth of Lorn. 553 km 2 of data were collected during 2012-2013 as part of the INIS Hydro (Ireland, Northern Ireland and Scotland Hydrographic Survey) programme.The area proves to consist of bedrock-dominated seabed, divided into narrow, stratigraphicallyconstrained and glacially-over-deepened basins. The bedrock is composed of late Proterozoic Dalradian metasediments overlain unconformably by Old Red Sandstone (ORS) sediments and lavas of ?Silur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 26 publications
1
20
0
1
Order By: Relevance
“…(, ), Hill (), Holden (), Hollingworth (), Howarth (, b, c, d), Howe et al . (), Huddart (, ), Huddart & Bennett (), Hughes (, ), Hughes et al . (, ), Jansson & Glasser (), Johnson (, b) Johnson et al .…”
Section: References For Britice Glacial Map V2unclassified
“…(, ), Hill (), Holden (), Hollingworth (), Howarth (, b, c, d), Howe et al . (), Huddart (, ), Huddart & Bennett (), Hughes (, ), Hughes et al . (, ), Jansson & Glasser (), Johnson (, b) Johnson et al .…”
Section: References For Britice Glacial Map V2unclassified
“…Bailey et al, 1924;Sissons, 1983;Peacock et al, 1989;Benn & Evans, 1993;Ballantyne, 1999;Golledge, 2010), until recently relatively little work has been conducted on the adjacent marine areas of the continental shelf (Baltzer et al, 2010;Peacock et al, 2012). New bathymetry data acquired from the Inner Hebrides have permitted Howe et al (2012Howe et al ( , 2015 and Dove et al (2015) to carry out broad-scale mapping of the seabed geology and geomorphology. However, there has been no detailed study relating the Late Quaternary offshore stratigraphy to the observed landform assemblages, or that explores the role of relative sea-level (RSL) change on ice sheet retreat.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…existing multibeam bathymetry data, newly gridded to best-possible horizontal resolution. These enabled novel interpretations of previously undetected features, or modified interpretations (from Dove et al, 2015;Howe et al, 2015) on the basis of the new observations; 3. new sediment core data from the study area;…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…At a more local scale, the geomorphological and sedimentary archives of the west coast fjords of Scotland augment the terrestrial evidence for the later stages of deglaciation of the last British-Irish Ice Sheet and the subsequent re-expansion of glaciers in the north and west Highlands during the Loch Lomond (Younger Dryas) Stade McIntyre and Howe, 2010;McIntyre et al, 2011;Howe et al, 2015b;Audsley et al, 2016;Small et al, 2016). The fjord sediments also record palaeoenvironmental changes during the Holocene (Howe et al, 2002;Nørgaard-Pedersen et al, 2006;Baltzer et al, 2010;Cage and Austin, 2010;Cundill and Austin, 2010;Mokeddem et al, 2010) and form sinks for organic carbon from terrestrial sources (Burrows et al, 2014).…”
Section: The Quaternary Of Scotlandmentioning
confidence: 87%